Mesenchymal Cells are a Promising -But Still Unsatisfying- Anti- Inflammatory Therapeutic Strategy for Osteoarthritis: A Narrative Review - Rosini, Sergio; Saviola, Gianantonio; Comini, Laura; Molfetta, Luigi (Current Rheumatology Reviews, 2023)
Osteoarthritis (OA) is a chronic disease with both degenerative and inflammatory characteristics, affecting the osteochondral unit with the involvement of cartilage, subchondral bone and periarticular tissues. OA can produce chronic pain with neuropathic and inflammatory characteristics, leading to an increased disability. OA is secondary to many predisposing factors where the inflammatory process plays a key role. To manage OA, it would seem logical to block the factors influencing the inflammatory process at different levels, T lymphocytes, neutrophils, and the balance between phenotype-1 macrophages (M1, pro-inflammatory) and phenotype-2 macrophages (M2 anti-inflammatory), the managing cells. The efforts to repair and rebuild the lost cartilage and the attempts to implant autologous or heterologous material, with or without growth factors and the administration of drugs or the use of medical devices, have failed their objective. TNF-alpha and IL-1 inhibitors can only have a transient effect on pain; intra-articular oxidized Low-Density Lipoproteins are able to stimulate the activation of M2, while growth factors need to be better investigated. Also, intra-articular injections of mesenchymal stem cells (MSC) can inhibit the proliferation of T-lymphocytes, leading to cartilage repair and to osteophytes inhibition thanks to the release of exosomes, nanosized particles which are the active components. Gut microbiota has a potential role in the development of OA and could be able to influence the response to therapeutic agents.
Keywords: synovium